Застосування оптимізаційних методів для вирішення задач підвищення енергоефективності електроенергетичних систем - Ягуп, Валерій Григорович; Ягуп, Катерина Валеріївна (Національний технічний університет "Харківський політехнічний інститут", 2018)
Стаття присвячена розробці і дослідженню методів оптимізації режимів систем електропостачання електротехнічних комплексів і систем з несиметричними і нелінійними навантаженнями з метою підвищення енергетичних показників і розрахунку параметрів симетро-компенсуючих пристроїв та силових активних фільтрів, що забезпечують оптимальні режими з допомогою математичних і комп'ютерних моделей і з застосуванням пошукової оптимізації, реалізованої з використанням сучасних програмних засобів комп'ютерної математики.

The thesis is devoted to the development and research of methods for optimizing the modes of power supply systems for electrotechnical complexes and systems with asymmetric and nonlinear loads in order to increase energy parameters and calculate the parameters of symmetric-compensating devices that provide optimal modes by means of mathematical and computer models and using search optimization implemented using modern software of computer mathematics. Generalized algorithms for implementing search optimization using modern computer software packages have been developed. The possibilities of applying various optimization criteria for solving the problems of increasing the power indicators of power supply systems with asymmetrical and non-linear loads are shown.
Application of optimization methods for solving the problem of enhancing energy efficiency of electric power engineering systems
Keywords: симетро-компенсуючий пристрій; силовий активний фільтр; змінні оптимізації; критерій оптимізації; symmetric-compensating device; power active filter; optimization variables; optimization criterion